Effectiveness of forest residue mulching in reducing post-fire runoff and erosion in a pine and a eucalypt plantation in north-central Portugal - Prats, Sergio A. (2019)
Fire-enhanced runoff generation and erosion are an important concern in recently burnt areas worldwide but their mitigation has received little public and scientific attention in Portugal. The present study addressed this knowledge gap for the two principal fire-prone forest types in Portugal, testing the effectiveness of a type of mulch that is widely available in the study region but has been little utilized and poorly studied so far. For logistic reasons, two somewhat different forest residue mulches were tested in a eucalypt plantation (eucalypt chopped bark) and a nearby Maritime Pine stand (eucalypt logging slash). Arguably, however, more important differences between the two study sites were those in fire severity, resulting in an elevated litter cover prior to mulching at the pine site but not at the eucalypt site, and in experimental design, with eight bounded erosion plots of 16 m2 installed at the eucalypt site as opposed to only four at the pine site (due to its limited size). Mulching was applied four months after the wildfire and two months after installation of the plots. Rainfall, runoff and sediment and organic matter losses were measured on a 1- to 2-weekly basis. Mulching proved highly effective at the eucalypt site, on average reducing the runoff coefficient from 26 to 15% and sediment losses from 5.41 to 0.74 Mg ha− 1. This mulching effect was also statistically significant, albeit only for the more important runoff and erosion events, and corresponded to a significant role of litter cover in explaining the variation in runoff and erosion. At the pine site, by contrast, mulching had no obvious effect. In all probability, this was first and foremost due to the comparatively small amounts of runoff and sediments produced by the untreated pine plots (5% and 0.32 Mg ha− 1) and, as such, due to the extensive needle cast following a low severity fire.